Prmt1 upregulated by Hdc deficiency aggravates acute myocardial infarction via NETosis - Zhiwei Zhang; Suling Ding; Zhe Wang; Xiaowei Zhu; Zheliang Zhou; Weiwei Zhang; Xiangdong Yang; Junbo Ge (Elsevier, 2022)
Neutrophils are mobilized and recruited to the injured heart after myocardial infarction, and neutrophil count has been clinically implicated to be associated with coronary disease severity. Histidine decarboxylase (HDC) has been implicated in regulating reactive oxidative species (ROS) and the differentiation of myeloid cells. However, the effect of HDC on neutrophils after myocardial infarction remains unclear. Here, we found that neutrophils were disorderly recruited into the ischemic injured area of the myocardium of Hdc deficiency (Hdc−/−) mice. Moreover, Hdc deficiency led to attenuated adhesion but enhanced migration and augmented ROS/neutrophil extracellular traps (NETs) production in neutrophils. Hdc−/− mouse-derived NETs promoted cardiomyocyte death and cardiac fibroblast proliferation/migration. Furthermore, protein arginine methyltransferase 1 (PRMT1) was increased in Hdc−/− mouse-derived neutrophils but decreased with exogenous histamine treatment. Its expression could be rescued by blocking histamine receptor 1 (H1R), inhibiting ATP synthesis or reducing SWItch/sucrose non fermentable (SWI/SNF) chromatin remodeling complex. Accordingly, histamine or MS023 treatment could decrease ROS and NETs ex vivo, and ameliorated cardiac function and fibrosis, along with the reduced NETs in plasma in vivo. Together, our findings unveil the role of HDC in NETosis by histamine-H1R-ATP-SWI/SNF-PRMT1-ROS signaling and provide new biomarkers and targets for identifying and tuning the detrimental immune state in cardiovascular disease.